The Use of Speech Act Functions for Women in the 2020 International Women’s Day Demonstration in Jakarta: Feminist Study - Fauzi, Aziz; Andayani, Andayani; Rohmadi, Muhammad (Society, 2022)
This study uses a descriptive qualitative method to classify and analyze the use of speech act functions in the International Women’s Day 2020 demonstration event in Jakarta. The research strategy used is content/document analysis. This strategy was used because the study would analyze data in sentences in the International Women’s Day 2020 demonstration poster. Data collection was carried out using the document and note-taking. In addition, the data analysis process uses content/document analysis. This analysis will dissect a speech/sentence in the research data to explain or analyze it in depth. The study results show that the action participants use the speech act function in various ways. The speech act functions are 11 data assertive functions, 17 data directive functions, 5 data expressive functions, and 12 declarative data functions. The directive function dominates the use of the speech act function. This is because, in demonstration activities, the speaker will make more requests (directives) in the form of demands on the interlocutor to solve all the problems presented by the speaker (demonstrator).